The effects of methylphenidate on cognitive performance of healthy male rats - Rostron, Claire L.; Kaplan, Elise; Gaeta, Victoria; Nigriello, Rachel; Dommett, Eleanor J. (Frontiers in Neuroscience, 2013)
We aimed to investigate the effects of methylphenidate (MPH) in healthy rats on two distinct radial maze tasks which rely on brain structures and neurotransmitters known to be affected by MPH: the Random Foraging Non-Delay Task (RFNDT) and the Delay Spatial Win Shift Task (DSWT). Hooded Lister rats were trained to complete either the RFNDT or the DSWT having received oral treatment of either a vehicle or MPH (3.0 mg/kg and 5.0 mg/kg for RFNDT, 3.0 mg/kg for DSWT). We found no effect of MPH on the RFNDT relative to the control group. However, those treated with 5.0 mg/kg MPH did take significantly longer to reach criterion performance than those treated with the 3.0 mg/kg MPH, suggesting some doses of MPH can have detrimental effects. For the DSWT, if MPH was present in both phases, performance did not differ from when it was absent in both phases. However, when present in only one phase there was an increase in errors made, although this only reached significance for when MPH was present only in the test-phase. These data suggest that MPH may have detrimental effects on task performance and can result in state dependent effects in healthy individuals.